Drivers of online purchase intention on Singles' Day: a study of Chinese consumers. (2017) - Zhao, Xiaqing; Wan, Hooi Lai
The purpose of the present study is to understand the drivers of Chinese consumers online purchase intention on Singles' Day. Data were collected from 214 Chinese consumers who have online purchase experience on Singles' Day. The results show that consumers online purchase intention is positively related to promotion, e-store atmosphere, word of mouth, and advertising and consumption rituals with either direct or indirect relationship with mediators such as perceived value, shopping enjoyment, impulsive buying orientation, and browsing. More specifically, advertising and consumption rituals exhibit a stronger influence among all drivers. The empirical evidence of this study will contribute to the literature in online shopping purchase intention as little research has addressed drivers of consumers online purchase intention on Singles' Day.